How to minimize lock-in effects of programs for unemployed workers - Conny Wunsch (IZA World of Labor, 2016)
Activation programs, such as job search assistance, training, or work experience programs for unemployed workers, typically initially produce negative employment effects. These so-called “lock-in effects” occur because participants spend less time and effort on job search activities than non-participants. Lock-in effects need to be offset by sufficiently large post-participation employment or earnings for the programs to be cost-effective. They represent key indirect costs that are often more important than direct program costs. The right timing and targeting of these programs can improve their cost-effectiveness by reducing lock-in effects.
Keywords: J68; 330; skills-training programs; program evaluation; lock-in effects